The Hydrothermal Optimal Load Flow, A Practical Formulation and Solution Techniques Using Newton's Approach - El-Hawary, M. E.; Tsang, D. H. (IEEE transactions on power systems, 1986)
This paper is concerned with the problem of optimal power flow in a hydro-thermal electric power system (HTOPF). The formulation and optimality conditions for systems with fixed head hydro-plants subject to an energy limited constraint are presented. The solution to obtain the optimal operational strategy is implemented using Newton's method. Due to the large scale nature of the problem, special sparsity oriented and structural property enhancements are explored and four versions for algorithmic implementation are detailed in the paper. Special attention is paid to finding realistic initial guess estimates for the algorithms reported. Results of computational experience with six standard test systems are reported in the paper.